2020
DOI: 10.1039/c9ta12492f
|View full text |Cite
|
Sign up to set email alerts
|

Iridium motif linked porphyrins for efficient light-driven hydrogen evolution via triplet state stabilization of porphyrin

Abstract: New iridium motif linked porphyrin TBPyZnP-Ir is developed for highly efficient photocatalytic hydrogen evolution (PHE) coupled with non-noble-metal cobaloxime co-catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…We fabricated a set of photocatalytic systems by employing Ir-1 and Ir-2 as PSs, TEA as the sacrificial donor, water as the proton source, and the organic solvent MeCN for dissolving PSs and making homogeneous solution with water . The PHE results of photocatalytic systems are shown in Figure , and the corresponding results are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We fabricated a set of photocatalytic systems by employing Ir-1 and Ir-2 as PSs, TEA as the sacrificial donor, water as the proton source, and the organic solvent MeCN for dissolving PSs and making homogeneous solution with water . The PHE results of photocatalytic systems are shown in Figure , and the corresponding results are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Photoactive metal complexes based on transition metals, for example, iridium, ruthenium, copper, and so forth, have attracted much attention for utility as photosensitizers (PSs) in artificial energy conversion systems, such as photocatalytic hydrogen evolution (PHE). One aspect of these complexes which makes them particularly useful in photocatalytic processes is their ability to absorb visible light, thereby inducing metal-to-ligand charge-transfer states, followed by charge separation and transportation. When designing photocatalytic systems with such light-harvesting species, it is of vital importance to minimize the structural complexity of the PS and maximize its ability to absorb photons. Among these types of systems, Ir­(III) complexes based on the bidentate N̂N ligand (typically 2,2′-bipyridine) have been included due to their functional properties, particularly since they are brilliant candidates for PHE reactions, owing to their unique photophysical properties such as long emission lifetime, good photostability, and high Stokes shift. It is well known that by controlling the nature and position of the functional substituents on the chelating ligands, the corresponding Ir­(III) complexes could be manipulated in terms of their electronic and chemical properties, giving way to electrochemical versatility and tunability. The modification of ligands to design metal complexes with certain functionalities, for example, PHE, can greatly influence the photoredox properties and efficiency of electron transfer in the complexes. So far, various photocatalytic systems have been studied in order to investigate the capacity of Ir­(III) complexes for PHE; these systems typically consist of a mononuclear bis-cyclometalated complex, [Ir­(ĈN) 2 (N̂N)] + (where ĈN = 2-phenylpyridine and N̂N = 2,2′-bipyridyl), transition metal cocatalyst, sacrificial electron donor, and water source to facilitate a suitable photoinduced electron transfer cycle, ultimately resulting in the reduction of hydrogen ions (H + ) to H 2 . By mimicking natural photosynthetic pathways, using systems such as those described above, we can pave the way to developing new technologies for generating H 2 as a renewable energy source in an environmentally clean, economical, and efficient manner. Additionally, such Ir­(III) comp...…”
Section: Introductionmentioning
confidence: 99%
“…25 Such a higher s PL value of ZnP-T-Ir would increase the photogenerated electron transfer rate from the photoexcited states to the proton in the PHE and consequently give rise to a higher degree of proton reduction (vide infra). 21 Nanosecond transient absorption spectra studies (Fig. S3 †) were performed to further conrm the existence of FRET between the iridium-motif and porphyrin ring in the ZnP-T-Ir porphyrin complex.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Recently, we also observed that conjugation of an Irmotif to a porphyrin core could enhance the PHE due to the stabilization of triplet excited states of the porphyrin moiety via the heavy atom effect of Ir, but the energy transfer between them does not completely occur due to large steric strain between the iridium-motif and the porphyrin ring resulting from the direct conjugation of the iridium-motif to the mesoposition of the porphyrin ring. 21 A traditional PHE system contains a photocatalyst, a sacricial electron donor, a proton source and a cocatalyst such as Pt, Co(III)-based complexes and iron complexes. 20,[22][23][24][25][26] Since these previously reported cocatalysts are either expensive or not very photostable, developing cocatalyst-free PHE systems will be of great signicance to advance the PHE methodology.…”
Section: Introductionmentioning
confidence: 99%
“…21 Tritton et al, depicted TBPyZnP-Ir displayed higher photocatalytic hydrogen generation activity 16.12 mmol g P< h P< within 5 h of irradiation in triethylamine (TEA). 22 The success in designing new sensitizers and their molecular engineering of photosensitizers culminated over the periods in our group and in particular the porphyrin based sensitizers with a '4' based porphyrin sensitizers such as LG-5, LG-DtT, and LG-tT series of sensitizers which includes the replacement of the 4-ethynyl thiophene in the LG-5 moieties through the thieno thiophene (LG-tT) or dithieno thiophene (LG-DtT) which majorly acts as auxiliary acceptor and cyanoacrylic acid as anchoring group over the synthesized materials. [23][24][25] The power conversion and the photocatalytic hydrogen generation efficiencies of the materials over the Pt-HPT/cTiO 2 moiety as 10.20%, 8.25% and 7.05%, respectively with hydrogen generation efficiency of 2691, 6641 and 7396 @# g -1 h -1 of PHPT-LG5, PCT-LG-DtT, PCT-LG-tT respectively.…”
mentioning
confidence: 99%